Myoepithelial carcinoma of palate: Case report - Balakrishnan Thayumanavan; Nandimandalam Venkata Vani (Wolters Kluwer Medknow Publications, 2014)
Myoepithelial carcinoma is an uncommon malignant salivary gland neoplasm with a predilection for parotid gland. However, its occurrence in minor salivary glands is considerably less with only 28 cases being reported in the literature. We report a case of myoepithelial carcinoma of palate in a 50-year-old woman. Computed tomography and magnetic resonance imaging revealed an extensive lesion in the palate. Microscopically, the tumor exhibited a wide spectrum of cytomorphologic features that overlap with other salivary gland tumors. Immunohistochemistry served as an adjunct in the diagnosis of the lesion. Clinical, radiographic, and histopathologic correlation along with immunohistochemical profile enabled to arrive at a diagnosis of myoepithelial carcinoma.